(untitled) (East West Medical College Journal, 2026)
Background: In orthopedic practice femoral neck fractures are a commonly encountered injury and that result in signiûcant morbidity and mortality. Objective: The aim of this study was to assess the postoperative complications of femoral neck fractures treated with biplane double supported screw fixation method. Methodology: This was a single group prospective hospital based clinical trial and was conducted in the Department of Orthopedic Surgery in Chittagong medical college hospital for a period of one and half year from July 2018 to July 2020. Sample size was 30 with (AO /OTA-31B) fracture as per set criteria treated with BDSF enrolled through inclusion and exclusion criteria. Result: Most of the study population (36.7%) was in 18-35 years. The mean age of the patients was 41.87 ± 13.950 years (range: 18-65 years). There was male predominance with male to female ratio about 3:1. maximum of the cases (66.7%) were due to RTA. Left side was affected in majority of the cases (56.7%). Maximum (53.3%) patient’s operation after injury time was at 10-14 days (mean ± SD: 10.27 ± 2.690 days) and duration of operation was within 45-60 minutes in about 53.3% patients (mean ± SD: 65.05 ± 13.856 minutes). There was no superficial infection, deep infection, hip stiffness or AVN. 02 patients dropped out at 3rd and 4th follow up. Out of 28 patients only 01 (3.6%) patients had delayed-union and 02 (7.1%) patients had non-union. Conclusion: Following treatment for a Femoral Neck Fracture (FNF) using Biplane Double- Supported Screw Fixation (BDSF), post-operative problems include screw back-out, implant failure, avacular necrosis (AVN), and non-union (fracture not healing). EWMCJ Vol. 14, No. 2, July 2026: 187-190